Avaliação da resistência ao desgaste microabrasivo de ligas de Ti-Si-B e Ti-Zr-Si-B tratadas termicamente pela técnica ball cratering - Lopes, Diogo Plachi (2024)
Titanium and its alloys have attractive physical, chemical and mechanical properties, such as specific mechanical resistance, microstructural stability, resistance to corrosion in different media and biocompatibility characteristics, thus being widely used for the manufacture of medical/dental devices and components used in automotive, aeronautics and aerospace areas. In the case of joint components that act under friction, titanium alloys based on substitutional solid solutions present limited wear resistance when compared to Co-Cr-Mo and Ti-Al alloys, which have microstructures containing intermetallic phases of greater hardness. In Ti-Si-B alloys, TiB is used as a reinforcing material, while Ti6Si2B has Vickers hardness values close to 1000HV. However, information on metal matrix Ti-Si-B alloys containing Ti6Si2B precipitates is still limited in the literature. In this context, this study aimed to evaluate the wear resistance using the ball cratering technique of the alloys Ti-2Si-1B, Ti-6Si-3B and Ti10Si-5B Ti-2Zr-2Si-1B, Ti-2Zr-6Si- 3B and Ti-2Zr-10Si-5B (%-at.) containing microstructures of Ti-+TiB and Ti-+Ti6Si2B. These ternary alloys and with the addition of 2%at. zirconium, were prepared by arc melting followed by heat treatment (1200°C for 16h), both stages under an argon atmosphere, aiming to obtain equilibrium microstructures. The microstructural characterization of the alloys was conducted with the aid of X-ray diffractometry, optical microscopy, scanning electron microscopy (SEM) and energy dispersive spectrometry (EDS) techniques. Vickers microhardness measurements of the heattreated alloys were obtained using a load of 200gf for 15s. The microabrasive ball cratering wear tests of the heat-treated alloys were carried out dry and using AISI 52100 steel balls (25,4mm in diameter, with a hardness of 818HV) as a friction element, using a load of 200g, rotation of 200rpm per 60min. Details of the worn surfaces were obtained by confocal laser microscopy. The Ti-2Si-1B and Ti-2Zr-2Si-1B alloys presented a Ti-α matrix with TiB precipitates, while the other alloys presented Ti+Ti6Si2B microstructures, after heat treatment. The hardness values of the alloys varied in the ranges of 264-481.5HV and 296-453.5HV for the Ti-Si-B and Ti-Zr-Si-B alloys, respectively, which were increased with increasing quantity of Ti6Si2B in the microstructure, but without any significant change with the addition of Zr. The wear coefficients ranged from 9.14.10-5 to 7.84.10-7 mm³/N.m, where the Ti-2Zr-6Si-3B alloy presented the lowest values of volume loss, worn depth and wear coefficient. A gain in wear resistance was observed with the increase of Ti6Si2B in the alloy's microstructure, and a direct relationship with Vickers microhardness, due to the greater quantity of hard phases. The addition of zirconium provided a significant increase in wear resistance compared to ternary alloys. Two- and three-body abrasive wear mechanisms were more pronounced in alloys richer in Si and B, as well as the occurrence of adhesion wear mechanisms.